The Impact of Productive Zakat on the Development of Mustahiq Businesses in Kecamatan Tualang - Marsa, Salsabila; Arsyianti, Laily Dwi (IQTISHADIA, 2023)
The Covid-19 pandemic had a significant impact on the development of microbusiness. The restrictions of social activities decrease sales which have affected the capitalist economy. Productive zakat funds can be a solution in dealing with these problems. This research aims to determine the characteristics of mustahiq and their business and analyze the factors affecting mustahiq total revenue after distributing productive zakat during the Covid-19 pandemic and its impact. The contribution of research related to the effect of productive zakat can be helpful for several parties, such as the government, zakat management organizations, especially BAZNAS Siak Regency, and academics. The method used is descriptive analysis, multiple linear regression analysis, and paired t-test. The results showed a difference in the total revenue of business before and after productive zakat distribution during the Covid19 pandemic. The factors that positively and significantly affect business total revenue after the issuance of productive zakat during the Covid-19 are capital, the number of zakat funds, dummy education, and dummy business type. The business duration affects negatively and significantly; however, the respondents' age doesn't affect total revenue increments significantly.